Суспільний простір поліетнічного міста як фактор формування етнічної толерантності молоді - Афанасьєва, Людмила Василівна; Афанасьева, Людмила Васильевна; Afanasieva, Liudmyla V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Толерантність формується не однаково в різних сферах соціуму, особливо у випадках етнічних, національних та релігійних відмінностей. Тому це дослідження стосується суспільного простору міст із численною кількістю етнічних груп, різноманітних культур, конфесій, традицій, способів поведінки та зумовлених цим соціокультурних проблем. У статті здійснено узагальнене ставлення молоді до проблеми міжетнічних відносин з урахуванням обумовленості подальшого соціально-економічного, політичного й культурного розвитку суспільства та держави домінуючими в молодіжному середовищі інтересами, поглядами, цінностями. An increasing role of the ethnic factor in a social life of the poly-ethnic city inevitably raises the question of threat that can be hidden in inter-ethnic conflicts. The are important current issues to reveal the role of urban social environment in the formation of ethnic tolerance of the youth at the regional and local levels and to search ways for adjustment of inter-ethnical relations in the youth poly-cultural stratum of particular cities and regions with a sustained polyethnicity. Given that two thirds of current Ukraine ’s population lives in cities the conditions of life are shaped by the subjects of the urban environment and simultaneously affect the worldview of both a local part of the youth and that part moving for training or employment from villages. Therefore, in modern development conditions of Ukrainian society the formation of tolerant relations among youth is a strategic task, because predominantly the youth groups are to a great extent poly-cultural, and it is the tolerance as a person ’s quality that can help in preventing conflicts between young people and reaching mutual understanding in society.
Social Space of a Polyethnic City as a Factor Determining Ethnic Tolerance of the Youth
Keywords: місто; суспільне середовище; молодь; поліетнічність; етнічна толерантність; city; the social environment; the youth; poly-ethnic; ethnic tolerance